Islamic Political-Legal Analysis of the Misuse of Night Entertainment Licensing in Medan City - Muhammad Farhan Akbar; Khalid Khalid (Hakamain: Journal of Sharia and Law Studies, 2025)
This study provides an Islamic political-legal analysis of the misuse of night entertainment licensing in Medan City, with a focus on the failure of regulatory enforcement under Mayor Regulation Number 3 of 2017. Although authority has been delegated to the Investment and One-Stop Integrated Services Office (DPMPTSP), the proliferation of unlicensed venues and ineffective oversight reveal systemic weaknesses in governance. Using an Empirical Legal Studies (ELS) approach, the research integrates statutory analysis, a living case study, and Islamic constitutional theory (Siyasah Dusturiyyah) to examine the intersection between legality and moral responsibility. The findings demonstrate that administrative complexity, poor inter-agency coordination, and intentional regulatory evasion have contributed to widespread non-compliance. From the perspective of Islamic governance, such violations constitute tamarrud (rebellion) against legitimate authority and a failure to uphold the principles of al-‘adalah (justice) and maslahah (public welfare). Drawing on the works of Al-Mawardi, the study argues that the state possesses both legal and religious legitimacy to enforce public regulations in the interest of community welfare. This research contributes to the broader discourse on Islamic public law by offering a normative framework for integrating religious ethics into modern regulatory systems. It recommends the development of digital licensing mechanisms, strengthened oversight, ethical governance, and engagement with religious institutions to ensure policy compliance. Ultimately, the study affirms that effective regulation in Muslim-majority societies must harmonize state law with Islamic values to safeguard justice, legitimacy, and social stability.